The Cornea in Keratoconjunctivitis Sicca - Pflugfelder, Stephen C. (Exp Eye Res, 2020)
The lacrimal functional unit (LFU) regulates tear production, composition, distribution and clearance to maintain a stable protective tear layer that is essential for maintaining corneal epithelial health. Dysfunction of the LFU, commonly referred to as dry eye, leads to increases tear osmolarity and levels of inflammatory mediators in tears that cause ocular surface epithelial disease, termed keratoconjunctivitis sicca (KCS). Corneal changes in KCS include glycocalyx loss, barrier disruption, surface irregularity inflammatory cytokine/chemokine production, cornification and apoptosis. These can reduce visual function and the increased shear force on the corneal epithelium can stimulate nociceptors sensitized by inflammation causing irritation and pain that may precede frank clinical signs. Therapy of keratoconjunctivitis sicca should be tailored to improve tear stability, normalize tear composition, improve barrier function and minimize shear forces and damaging inflammation to improve corneal epithelial health.